FBXO32 activates NF-κB through IκBα degradation in inflammatory and genotoxic stress. (November 2017) - Meshram, Sachin N.; Paul, Debasish; Manne, Rajeshkumar; Choppara, Srinadh; Sankaran, Ganga; Agrawal, Yashika; Santra, Manas Kumar
Graphical abstract: Abstract: In response to diverse stresses, the canonical NF-κB pathway gets activated primarily to protect the cells and maintain their genomic integrity. It activates the cell cycle checkpoints allowing the cells with limited damage to restore a normal life cycle. One of the key events in activation of the canonical NF-κB pathway is the selective proteasomal degradation of IκBα. It has been previously shown that F-box protein βTRCP1 has limited role in directing the proteasomal degradation of IκBα during stress conditions. Here, we report another member of F-box family proteins, FBXO32, as a potential activator of NF-κB signaling during genotoxic stress and inflammatory response. Following genotoxic or inflammatory stress, FBXO32 is stabilized, which leads to polyubiquitination and proteasome mediated degradation of IκBα. We also found that FBXO32 is required for physiological regulation of IκBα levels in unstressed cells. Thus, we decipher the new role of FBXO32 in regulation of NF-κB signaling pathway.